O estado somatotrófico é um determinante importante da ação do hormônio tiroideano em crianças com deficiência de hormônio de crescimento: implicações para a terapia com levotiroxina no hipotiroidismo central - Martins, Manoel Ricardo Alves [UNIFESP] (2007)
Context: The biological significance of GH-induced changes in serum TH concentrations is unknown. It has been suggested that serum FT4 should be targeted at the high normal range during GH replacement. Objective: To evaluate the effects of GH replacement on thyroxine biological effects. Hypothesis: If GH modulates thyroxine biological effects, serum FT4 should be targeted accordingly. Design/Setting: Observational (Study 1) and interventional (Studies 2- 3)/Outpatient. Patients: 32 GHD patients (13 off GH; 22 on L-thyroxine). Interventions: Study 2: Levothyroxine to increase FT4 (>1.0ng/dL). Study 3: GH administration or withdrawal. Main outcome measures: FT4, TT3, myocardial isovolumic contraction time (ICT) and resting energy expenditure (REE). Results: Study 1: OFF GH and ON GH groups had similar FT4, but OFF GH showed lower TT3 (P<0.01) and REE (P=0.02), higher ICT (P<0.05) than ON GH and controls. On GH, ICT and REE correlated only with TT3 (r=-0.48, r=0.58, P<0.05). Off GH, ICT correlated only with FT4 (P<0.01). Study 2: Off GH, levothyroxine intervention increased FT4 (P=0.005), TT3 (P=0.012), decreased ICT (P=0.006), increased REE (P=0.013); ICT and FT4 changes correlated (r=-0.72, P=0.06). On GH, levothyroxine increased FT4 (P=0.0002), TT3 (P=0.014), REE (P=0.10), decreased ICT (P=0.049); REE and TT3 changes correlated (r=0.60, P=0.05). Study 3: GH decreased FT4, increased TT3, decreased ICT, increased REE (P<0.05). REE correlated (P<0.05) with IGF-I (r=0.57), TT3 (r=0.64). ICT correlated only with TT3 (r=-0.47). Conclusions: GH replacement improves the biological effects of thyroxine. Serum FT4 should be targeted at the high normal range in GHD patients only off GH replacement.